Penguatan Karakter Cinta Sholawat Pada Santri Melalui Pendampingan Ekstraulikuler Hadroh di Madin Miftahul Ulum Kesugihan Pulung Ponorogo - Ririn Supiyah; Hanafi Hadi Susanto (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic education is education that aims to form a complete human personality, form the character of love and prayer through hadroh extracurriculars which are closely related to religion. This study aims to find out the steps taken to strengthen the character of the love of prayer for students through Hadroh extracurricular assistance at Madin Miftahul Ulum Kesugihan Pulung Ponorogo. The method used in this research is Asset Based Community Development (ABCD). The stages of dedication using the ABCD method are contained in 5 (five) mentoring steps, namely discovery, dream, design, define, and destiny. The results of the study show that the steps taken to strengthen the character of the love of sholawat are carried out by introducing the figure of Rasulullah SAW, the exemplary attitude of Rasulullah SAW.